Design of Data Security Module Using Key-Policy Attribute Based Encryption (KP-ABE) Algorithm for an Internet-of-Things System - Reza Fahlevi; Muhammad Salman (Jurnal Penelitian Pendidikan IPA, 2024)
Internet becomes more popular over time. Everything can be connected with the internet with larger coverage area which makes everyone have a higher dependence on it. Along with that, internet-based technology development and application is also moving to its best pattern. In the development, there are a lot of devices that can be used for Internet-of-Things system development. However, Internet-of-Things system has the following security vulnerabilities especially for access control and data protection. For the data privacy protection, it becomes more critical especially when using a standard TCP/IP based application layer protocol to secure the data before its transmitted from the client to the server. This work will be focused on the data privacy security development using a cryptographic scheme for Internet-of-Things system. Attribute Based Encryption (ABE) is one of cryptographic scheme that can be one of the best choices for data protection implementation in embedded device using NVIDA Jetson Nano. It will demonstrate the design of Key-Policy Attribute Based Encryption (KP-ABE) scheme to generate a symmetric key that will be used for Advanced Encryption Standard (AES) while encryption and decryption process. The result shows the execution time of key generation, data encryption and decryption using unique number of attributes.